Pajak Penghasilan Pasal 24 dan Pajak Penghasilan Pasal 25 - Putri Ahmarani; Desi Elisa Fitri; Khairunnisa Aulia Hrp (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The rules for tax reduction/credit for taxes paid are explained in PPh Article 24. abroad compared to the total PPh payable in Indonesia. Among the tax objects are various forms of foreign income, determined by calculating the Article 24 tax credit which selects the lesser of the maximum international tax credit limit and the tax actually paid abroad. Requesting a foreign tax credit must be paid with a foreign tax payment document. Significant changes reporting foreign income requires updating the tax return. PPh Payment of income tax installments every month of the year is covered in Article 25. The tax clock is running. To apply for foreign tax credits, taxpayers must reduce the amount of tax due. PPh article 25 must be paid. It is owned by the Taxpayer and must be paid by the deadline fifteen months after the end of the Tax Period. the penalty for late payment is a monthly interest rate of 2%. The calculation of Income Tax Article 25 is carried out using the previous year's income minus tax credits, calculated at various rates for certain individual entrepreneur taxpayers as well as corporate taxpayers.